Uma isca muito apetitosa: Como o caderno de gastronomia de um grande jornal no Ceará vende o termo cozinha regional - Campelo, Ana Paola Vasconcelos (2019)
The research has as its central theme aspects related to northeastern regional cuisine, with special focus on Ceará’s cuisine. As a methodology, it performs a quantitative and qualitative documentary analysis of the terms and contents related to the regional cuisine published in the gastronomic section of the Diário do Nordeste newspaper – a communications vehicle of circulation throughout Ceará –, from 2014 to 2018. Thus, the objective of this research is to study how this newspaper presents the term regional cuisine and its variations, analyzing the spaces, the shapes, the highlights, the characterizations given to the various products of this category in the media. The idea of the research is to have the opportunity to understand a little more about the different perspectives cast by this newspaper about the typical cuisine of the region. Among the findings of the study are 20 terms compatible with “regional cuisine”, records of typical preparations of this cuisine, besides the observation of characterization patterns around the typification of the restaurants/events involved in the analysis. Regarding the main characterizations of regional cuisine contained in the texts of the materials, three patterns were identified. The first, “Proudly Regional,” deals with the eminently regional restaurant / event that uses no subterfuge to characterize its menu, production, and environment. The second pattern is “Regional as bait”, in which the restaurants / events featured in the daily newspaper Diário do Nordeste often use regional cuisine as a way of attracting attention to themselves, even if clearly this type of cuisine is not part of it, of your proposal. The third and final pattern, “Regional without a regional face”, as its name implies, presents a regionally uncharacterized, so as to “repaginate”, leave “different”, “transform simple food into something more exquisite”.